SHARI’AH BYLAWS IN INDONESIA AND THEIR IMPLICATIONS FOR RELIGIOUS MINORITIES (JOURNAL OF INDONESIAN ISLAM, 2011)
This article examines the implementation of shari’ah bylaws as a response to the regional autonomy law passed in 1999 and their implications for religious minorities. Under this regional autonomy regulation, local governments at the district level have authority to issue their own regulations. There are three broad sets of issues in Indonesian shari’ah bylaws: public order and social problems, religious skills and obligations, and religious symbolism. The article argues that the introduction of such bylaws has many negative implications for religious minorities in Indonesia. This is, it further argues, because many of religious minority groups are forced to observe the same regulations as mainstream Muslims. Shari’ah bylaws, it goes on to say, have also caused discrimination against religious minorities. Attempts to keep wary eyes on the the negative implications of the enactment of shari’ah bylaws need, therefore, to be undertaken. This responsibility is not in the hands of the government, but also Muslim communities at large. The Indonesian government must treat all social and religious groups equally, guaranteeing no discrimination against each of them. Muslim communities are deeply in need of exploring and practicing the substance, and not the formal aspects, of shari’ah.